The relationship between spousal support and anxiety in third trimester pregnant women facing childbirth: at the Godean II Community Health Center. - Putri Reiniyah Hasan Hasan; Diah Nur Annisa; Sarwinanti Sarwinanti (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: The third trimester of pregnancy is a phase of preparation for childbirth that is often accompanied by anxiety in pregnant women. Physical and psychological changes that occur can affect the mental readiness of mothers. Spousal support is an important factor in reducing anxiety levels prior to childbirth. Purpose: The purpose of this study was to determine the relationship between husband support and anxiety in pregnant women in the third trimester in facing childbirth. Method: This study used a quantitative research design with a descriptive correlational approach and a cross-sectional time frame. Results: Analysis of the data using Spearman's rank correlation coefficient yielded a correlation coefficient of -610 with a significance of 0.000. Because the p-value was ≤0.05, Ho was rejected and Ha was accepted, meaning that there was a significant relationship between spousal support and the anxiety of pregnant women in their third trimester in facing childbirth. Conclusion: Spousal support affects the anxiety of pregnant women in their third trimester facing childbirth.